Liquid-Liquid Equilibrium of Aqueous Two-Phase Systems Containing PPG725 and Potassium Salts at 298.15 K - Liu, Rong; Yan, Yongsheng (Asian Journal of Chemistry, 2015)
The binodal data and tie-line data for the PPG725-KOH/K2CO3/K3PO4 aqueous two-phase systems were determined at 298.15 K. Three empirical equations were used to correlate the binodal data and obtained good fit effect. The tie-line composition was correlated by the Othmer-Tobias and Bancraft equations. Furthermore, the effect of salt on the binodal curve for the disquisitive systems have been discussed and it was found that anions with a higher valence are better salting-out agents than anions with a lower valence, which is corresponded to the value of salting-out coefficient and effective excluded volume values. In the investigated systems, the order of salting-out abilities of salts is K3PO4 > K2CO3 > KOH.